Réponses

2013-04-24T15:13:53+02:00
1) A=(3*(8/3)-1)^2-49
A=(8-1)^2-49=49-49=0

2) A=(3*0-1)^2-49
A=1-49=-48

3) A=(3x-1-7)(3x-1+7)
A=(3x-8)(3x-6)
A=0 ---> 3x-8=0 ou 3x-6=0 ---> x=8/3 ou x=6/3=2
Meilleure réponse !
2013-04-24T15:15:21+02:00

1)  A=(3*(8/3) -1)² - 49

=(8-1)² - 49

=7² - 49

= 49-49

=0

 

2) A= (3*0 -1)² - 49

=(-1)² - 49

= - 48

 

3) A = (3x - 1 ) ² - 49 = (3x -1)² - 7² = (3x-1+7)(3x-1-7)=(3x+6)(3x-8)

A = (3x+48)(3x-49) = 0

⇔3x+6=0     ou     3x-8=0

     3x= -6                 3x=8

      x= -2                   x= 8/3